Physical performance and sleep in athletes - Zimmermann, E. (Wiener Medizinische Wochenschrift, 1996)
To estimate the activity of the sympathetic nervous system excretion of noradrenaline (NA) and adrenaline (A) of members of national teams (8 different olympic disciplines) has been looked at. Measured by GC/MS the catecholamines showed some characteristics that can be expressed by the NA/A-ratio which is independent of sports-discipline, gender and age (17 to 35 years): morning-urine, representing sleeping-time, expressed good recreation with NA/A > 10 and nervousness followed by low performance with NA/A < 8. Athletes longing for good performance may be stressed by time-shift, high-altitude training or by sharing their sleeping-room with another person-but nevertheless there are most important parallels in the reaction we can see for students during examination-time, shift-workers and patients. The experience made by measuring NA/A during sleeping time of athletes allows to give some physiologically based explanation about effects of the sympathetic nervous system. So NA/A-ratio can become an easy to handle tool in the field of diagnostic and therapeutic work.